2010
DOI: 10.1038/sc.2010.146
|View full text |Cite
|
Sign up to set email alerts
|

A global map for traumatic spinal cord injury epidemiology: towards a living data repository for injury prevention

Abstract: Study design: Literature review. Objectives: To map traumatic spinal cord injury (TSCI) globally and provide a framework for an ongoing repository of data for prevention. Setting: An initiative of the ISCoS Prevention Committee. Methods: The results obtained from the search of Medline/Embase using search phrases: TSCI incidence, aetiology, prevalence and survival were analysed. Stratification of data into green/yellow/red quality 'zones' allowed comparison between data. Results: Reported global prevalence of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
229
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(245 citation statements)
references
References 55 publications
7
229
1
8
Order By: Relevance
“…7 The prevalence of NTSCI in this present study is at the lower end of the range reported for TSCI. 5 For Australia, the prevalence of TSCI reported was considerably greater, with a range of 370-681 per million. 5 It was not possible to report the prevalence by Frankel grades B and C as they were excluded from calculations in the reference paper because of insufficient numbers for credible data analysis as separate groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The prevalence of NTSCI in this present study is at the lower end of the range reported for TSCI. 5 For Australia, the prevalence of TSCI reported was considerably greater, with a range of 370-681 per million. 5 It was not possible to report the prevalence by Frankel grades B and C as they were excluded from calculations in the reference paper because of insufficient numbers for credible data analysis as separate groups.…”
Section: Discussionmentioning
confidence: 99%
“…5 For Australia, the prevalence of TSCI reported was considerably greater, with a range of 370-681 per million. 5 It was not possible to report the prevalence by Frankel grades B and C as they were excluded from calculations in the reference paper because of insufficient numbers for credible data analysis as separate groups. 15 The only other publication from Australia that reports on survival of persons with SCI 23 was not able to be used for this project because it records only survivorship at age of injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival rate of TSCI patients is 30% lower than that of the total population during the same period. 1,2 Because of the rapid development of industries and the industrial economy in China, the incidence of TSCIs has rapidly increased. However, due to lack of large samples and multi-center investigations, it is difficult to obtain accurate epidemiological data regarding the details of TSCIs across the country.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers can use this information to establish appropriate primary prevention programs. 6 This article will focus on the importance of primary prevention and will detail etiology-specific evidence-based SCI prevention tips.…”
mentioning
confidence: 99%